11 Haematology specialty registrars' training in palliative care. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Nightingale, Laura; Low, Joseph
Abstract : Background: Patients with haematological malignancies (HM) experience significant symptom burden, but uptake of palliative care services remains low, with most patients cared for by the haematology teams. Little is known about the training haematology specialty registrars (StRs) receive to enable them to provide palliative care to patients. Aims: This study aimed to explore haematology StRs' experiences of education and training in palliative care during specialty training, and how this could be improved. Method: A qualitative study using semi-structured interviews of 9 haematology StRS from the London Deanery was carried out. All interviews were audio-taped, transcribed verbatim and thematically analysed using Framework Analysis. Results: Four main themes emerged: different learning experiences, areas of difficulty, role of the specialist palliative care team (SPCT) and future improvements to education and training. Participants did not receive any formal specialty-specific training on palliative care and all participants felt that further teaching would be beneficial. Experiential learning was highly valued with confidence increasing after working in certain key specialties. Despite positive interactions with the SPCT, referral to them was often viewed as a sign of professional failure. However, all the StRs interviewed felt that earlier integration of the SPCT would be beneficial. Conclusion: Key areas where training could be improved, included increased focus on palliative care in the curriculum and formal specialty-specific teaching on palliative care in haematology. The SPCT play a vital role in education as well as service provision, with every clinical encounter being an opportunity to disseminate knowledge. The StRs wanted to learn from the SPCT in an observational capacity and the specialty should facilitate this by offering placements at hospices or with hospital palliative care teams. This would provide the opportunity for case-based, clinically relevant learning, a clinical imperative since these StRs are the consultants of the future.